PENGARUH PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DRIVER ONLINE GRAB DI YOGYAKARTA - Fahrurozi Ibnu Faiz; Ignatius Soni Kurniawan; Henny Welsa (Universitas Sarjanawiyata Tamansiswa, 2019)
The customer’s satisfaction is very important because it is able to increase the amount of the new costumer and the profit pf the company. The research is done to know the influence of the Price Perception and the Service Quality toward the costumer of Grab’s Online Driver in Yogyakarta. The research was done in Yogyakarta. The number data sampling are 100 respondents which was chosen randomly or Random Sampling Method. The collection of the data was done by spreading the questionnaire with using the 1 – 5 scale to measure the 23 indicator of questions. The result of the research is showing the result of the price perception variable influenced with the customer’s satisfaction, and the service quality influenced with the customer’s satisfaction. The coefficient of determination in this research is about 68.3% toward the costumer’s satisfaction.Keywords: Price Perception, Service Quality, and Costumer’s satisfaction